Telemedizinisch unterstütztes Screening der retinalen Gefäße („Talking Eyes”) - Michelson, Georg; Groh, M.; Groh, M. J.M.; Baleanu, D.; Harazny, J.; Horstmann, R.; Kolominsky-Rabas, Peter (Klinische Monatsblätter für Augenheilkunde, 2005)
Background: Cerebral and retinal vessels behave similarly under the influence of vascular risk factors. Several groups have shown that retinal microvascular abnormalities represent an independent risk factor with regard to strokes and heart attacks. Aim of the Study: The aim of this study was to perform a prospective screening examination with regard to retinal microvascular abnormalities as well as an extended vessel diagnosis in a subgroup of patients with lower arteriovenous risk values. Methods: In the course of a prospective cross-sectional study ("Talking Eyes") between 1.9.2001 and 1.8.2002 a telemedical-supported screening of the retina (study 1) was carried out in 7,163 subjects. The patients were selected without any inclusion or exclusion criteria. The mean age was 48.2 ± 8 years (18-83 years) with a sex distribution of 39.2% females to 60.8% males. Digital fundus photos of the right and left eyes were taken for all patients. The pictures were taken without pupil dilation using a CANON-NM camera. The pictures and case histories were stored in a central server using web-based software (MedStage, Siemens). In a central reading centre, the arteriovenous ratio of both eyes was determined telemedically using the Parr-Hubbard formula and the retinas subjected to a standardised examination by an ophthalmologist. The retinal risk factor was calculated on the basis of the arteriovenous ration, the presence of microvascular abnormalities and the case history. The reproducibility of measurement of the arteriovenous ratio (Kronbach alpha coefficient) was evaluated by double measurements on 1,332 images. In a subgroup of study 1 with arteriovenous ratio values < 0.76 (N = 107), an extended vessel diagnosis with measurement of 24-h blood pressure and vessel-relevant blood values (homocysteine, cholesterol, LDL, HDL, CRP, TG, HbA1c) was carried out (study II). Results: Study 1: The Kronbach alpha coefficient as a measure of reproducibility amounted to 0.77. The mean arteriovenous ratio of the retinal vessels was 0.83 ± 0.09 and showed a pronounced age dependence (R = 0.9, p < 0.0001). On multivariate testing the arteriovenous ratio correlated significantly (R = 0.33, p < 0.001) with the factors age, systolic blood pressure, diastolic blood pressure and body mass index. Diastolic blood pressure followed by age had the largest influence. The prevalence of microvascular abnormalities in the right (RE) and left (LE) eyes, respectively were: cotton wool foci RE 0.0015%, LE 0.003%, retinal haemorrhage RE 0.1%, LE 0.1%, focal stenoses RE 3.4%, LE 3.4%, tortuositas vasorum RE 4.1%, LE 4.0%, arteriovenous crossing signs RE 11.2%, LE 11.2%. On multivariate testing the occurrence of microvascular abnormalities correlated significantly (R = 0.38, p < 0.001) with the factors high blood pressure known from case history, body mass index, and gender. Arterial hypertension had the strongest influence followed by diastolic blood pressure. The calculated retinal risk factor correlated with the prevalence of angina pectoris. Study 11: 2/3 of the subjects with arteriovenous risk factor values < 0.76 exhibited pathologically high 24-h blood pressure values. For these patients there were significant correlations between the arteriovenous ratio and the low-density lipoprotein concentration as well as the Framingham risk score. Conclusion: In the course of a prospective, telemedical-supported screening examination of the retinal vessels of more than 7,000 subjects the arteriovenous ratio exhibited a strong dependence on age and blood pressure. Among the subjects with lowered arteriovenous ratio values, 2/3 exhibited arterial hypertension in the 24-h blood pressure determination.
Created from Fastlane, Scopus look-up
Keywords: Retinal mikroangiopathy; Screening; Talking Eyes; Telemedicine